Philosophy-Infused Culture-Based Learning Models In Mathematics Education - Mendrofa, Ratna Natalia; Dewi, Izwita; Simamora, Elmanani (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
The aim of this research is to explore and leverage the synergistic relationship between the philosophy of mathematics education and culture-based learning models. It seeks to investigate how philosophical perspectives can inform and enrich the development and implementation of culture-based learning models in mathematics education. Additionally, it aims to examine how integrating philosophical underpinnings can deepen students' comprehension of mathematical concepts within diverse cultural frameworks. Reading the entire paper is essential for anyone interested in advancing the field of mathematics education with a focus on cultural integration. This research explores the intricate relationship between the philosophy of mathematics education and culture-based learning models, offering valuable insights into how philosophical perspectives can enrich teaching practices within diverse cultural contexts. Moreover, it outlines crucial future research agendas, emphasizing the need for cross-cultural studies to identify universal and context-specific approaches, as well as the importance of equipping mathematics educators with the necessary skills through professional development programs. Overall, the paper provides a comprehensive roadmap for educators, researchers, and policymakers to promote inclusive and culturally relevant mathematics education, making it a must-read for those dedicated to enhancing educational practices in a diverse world. In conclusion, the integration of cultural elements in mathematics education is a dynamic field with promising future agendas. Cross-cultural research and teacher professional development programs are essential components for advancing the inclusivity and effectiveness of mathematics education in diverse contexts. By addressing these agendas, we can foster a more equitable and culturally responsive approach to teaching and learning mathematics.